2015
DOI: 10.1093/mnras/stv2033
|View full text |Cite
|
Sign up to set email alerts
|

Energies of GRB blast waves and prompt efficiencies as implied by modelling of X-ray and GeV afterglows

Abstract: We consider a sample of ten GRBs with long lasting ( 10 2 sec) emission detected by Fermi/LAT and for which X-ray data around 1 day are also available. We assume that both the X-rays and the GeV emission are produced by electrons accelerated at the external forward shock, and show that the X-ray and the GeV fluxes lead to very different estimates of the initial kinetic energy of the blast wave. The energy estimated from GeV is on average ∼ 50 times larger than the one estimated from X-rays. We model the data (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
157
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(176 citation statements)
references
References 72 publications
17
157
1
1
Order By: Relevance
“…Sironi & Spitkovsky 2009;Lemoine & Pelletier 2010;Sironi et al 2013) from the theoretical point of view, the low magnetization implied from recent broadband observations of the afterglows (e.g. Kumar & Barniol Duran 2009;Lemoine et al 2013;Santana et al 2014;Beniamini et al 2015;Zhang et al 2015) seems to be consistent with the theoretical argument.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Sironi & Spitkovsky 2009;Lemoine & Pelletier 2010;Sironi et al 2013) from the theoretical point of view, the low magnetization implied from recent broadband observations of the afterglows (e.g. Kumar & Barniol Duran 2009;Lemoine et al 2013;Santana et al 2014;Beniamini et al 2015;Zhang et al 2015) seems to be consistent with the theoretical argument.…”
Section: Introductionsupporting
confidence: 82%
“…Santana et al 2014;Zhang et al 2015) suggest much lower magnetization. Beniamini et al (2015Beniamini et al ( , 2016 pointed out that the high-efficiency problem in the prompt emission will be resolved by a very small ǫ B . In this case, the X-ray-emitting electrons are in the slow cooling regime, and the synchrotron flux in the X-ray band can be suppressed by the IC cooling.…”
Section: 4mentioning
confidence: 99%
“…Energy lost here ends up in the GRB afterglow. The latter process can be up to 50 per cent efficient (Beniamini et al 2015), meaning that the total isotropic equivalent energy release summed across all wavelengths is at least double the observed value of E γ,iso .…”
Section: The Magnetar Energy Budgetmentioning
confidence: 98%
“…However, if the internal energy is carried by thermal protons or confined cosmic rays, it is natural to expect the reconversion of the internal energy into the kinetic energy; see Appendix C. It has been shown that this effect increases the gamma-ray emission efficiency, represented by the ratio of prompt gamma-ray energy to afterglow kinetic energy, calculated in an approach where shells reflects off each other after colliding, i.e., collisions are not perfectly inelastic (Kobayashi & Sari 2001). Recent results on afterglow modeling also suggest a small value of the gamma-ray emission efficiency (Beniamini et al 2015).…”
Section: Synthetic Light Curvesmentioning
confidence: 99%